2023
DOI: 10.1002/eat.24083
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional associations between self‐esteem and problematic eating behaviors in adolescents

Desi Beckers,
William J. Burk,
Junilla K. Larsen
et al.

Abstract: ObjectiveTheories propose that low self‐esteem and problematic eating behaviors (PEBs) negatively impact each other. While previous studies suggested bidirectional associations between self‐esteem and PEBs, they did not separate within‐person from between‐person associations. Therefore, this prospective study investigated the within‐person bidirectional associations between self‐esteem and four PEBs in adolescence, while accounting for between‐person differences.MethodWe used two independent longitudinal sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This paradoxical association was accentuated by a strong auto-correlation between the state factors (Figure 3, Panel A). The same paradoxical association was seen between the within-individual adjusted cross-lagged effect (as Reanalyses of Beckers et al (2023) Our reanalyses with RI-CLPM confirmed the within-individual adjusted cross-lagged effects reported by Beckers et al (corresponding to effects cx and cy in Figure 1, Panel B) between self-esteem and problematic eating behaviors (Table 1, Row 1). However, similarly as in the simulations above, without any direct effects between X and Y scores, cross-lagged correlations between prior and subsequent person-mean centered levels of selfesteem and problematic eating behaviors had the opposite sign compared with the cross-lagged effects in RI-CLPM, i.e.…”
Section: Simulationssupporting
confidence: 87%
See 3 more Smart Citations
“…This paradoxical association was accentuated by a strong auto-correlation between the state factors (Figure 3, Panel A). The same paradoxical association was seen between the within-individual adjusted cross-lagged effect (as Reanalyses of Beckers et al (2023) Our reanalyses with RI-CLPM confirmed the within-individual adjusted cross-lagged effects reported by Beckers et al (corresponding to effects cx and cy in Figure 1, Panel B) between self-esteem and problematic eating behaviors (Table 1, Row 1). However, similarly as in the simulations above, without any direct effects between X and Y scores, cross-lagged correlations between prior and subsequent person-mean centered levels of selfesteem and problematic eating behaviors had the opposite sign compared with the cross-lagged effects in RI-CLPM, i.e.…”
Section: Simulationssupporting
confidence: 87%
“…and the two random intercepts (RI-X and RI-Y) were freely estimated. Reanalyses of Beckers et al (2023) We refer to Beckers et al (2023) for more comprehensive information on the study sample, used instruments, methodology, etc. In short, data are from the longitudinal Mental Health and Health Habits project, conducted in the Netherlands.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without this combination of expected effects, observed effects would appear to be spurious and conclusions of causality premature. We Sorjonen, Nilsonne, et al, 2024; have previously used this type of triangulation and challenged conclusions in studies using RI-CLPM and claiming effects of need of cognition on anxiety and depression symptoms (Zainal & Newman, 2022), of income on self-esteem (Bleidorn et al, 2023), of curiosity on creativity and vice versa (Ma & Wei, 2023), and of self-esteem on eating pathology and vice versa (Beckers et al, 2023). We recommend researchers to use similar triangulations to scrutinize findings from analyses of observational data.…”
Section: Discussionmentioning
confidence: 98%